PENINGKATAN KAPASITAS PEMASARAN UMKM MELALUI MEDIA PROMOSI AUGMENTED REALITY MENGGUNAKAN METODE LUTHER-SUTOPO - Elvi Rahmi; Andri Nofiar.Am; Armita Novriana Rambe; Septi Ayu Angrayni; Bayu Dani Kurniawan (Smart Education, 2026)
Abstract: Small and Medium Enterprises (SMEs) are required to adopt digital technologies to improve their competitiveness, particularly in marketing activities. However, most SMEs still rely on conventional promotional media that provide limited product information and low customer engagement. This study aims to develop an Augmented Reality (AR)-based promotional media using the Luther–Sutopo multimedia development method to enhance SMEs' marketing capacity. The research employed the Luther–Sutopo method, consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Data were collected through observation, interviews, documentation, and questionnaires. The developed system integrates an Admin Dashboard for product management and a WebAR-based public website that enables users to access three-dimensional product visualization, promotional videos, and detailed product information through a web browser without additional installation. System evaluation was conducted using Black Box Testing and User Acceptance Testing (UAT). The results indicate that all system functions operated properly, while the UAT achieved an average score of 93.67%, categorized as Highly Feasible. The findings demonstrate that the developed AR-based promotional media enhances product visualization, user experience, and digital marketing effectiveness, providing an innovative strategy to strengthen SMEs' competitiveness in the digital transformation era. Keywords: augmented reality; digital marketing; Luther–Sutopo; multimedia; SMEs. Abstrak: Usaha Mikro, Kecil, dan Menengah (UMKM) dituntut untuk memanfaatkan teknologi digital guna meningkatkan daya saing, khususnya pada aspek pemasaran. Namun, sebagian besar UMKM masih menggunakan media promosi konvensional yang memiliki keterbatasan dalam penyajian informasi produk dan interaksi dengan konsumen. Penelitian ini bertujuan mengembangkan media promosi berbasis Augmented Reality (AR) menggunakan metode pengembangan multimedia Luther–Sutopo untuk meningkatkan kapasitas pemasaran UMKM. Metode penelitian meliputi enam tahapan, yaitu concept, design, material collecting, assembly, testing, dan distribution. Data diperoleh melalui observasi, wawancara, dokumentasi, dan kuesioner. Sistem yang dikembangkan mengintegrasikan Dashboard Admin untuk pengelolaan produk dan Website Publik berbasis WebAR yang memungkinkan pengguna mengakses visualisasi produk tiga dimensi, video promosi, serta informasi produk secara interaktif melalui browser tanpa instalasi aplikasi. Pengujian sistem dilakukan menggunakan Black Box Testing dan User Acceptance Test (UAT). Hasil penelitian menunjukkan seluruh fungsi sistem berjalan sesuai dengan kebutuhan, sedangkan hasil UAT memperoleh nilai rata-rata 93,67% dengan kategori Sangat Layak. Temuan ini menunjukkan bahwa media promosi berbasis Augmented Reality mampu meningkatkan kualitas visualisasi produk, pengalaman pengguna, dan efektivitas pemasaran digital sehingga berpotensi menjadi strategi inovatif dalam meningkatkan daya saing UMKM di era transformasi digital. Kata kunci: augmented reality; pemasaran digital; Luther–Sutopo; multimedia; UMKM.